Use field-programmable gate array for formation of test signal impedance meter - Kolesnikov, V.A.; Baisagov, Ya.Zh. (Publishing House of the KarSU named after E.A.Buketov, 2013)
This article describes a method of generating test signals for bridge impedance meter with modern high-speed components . The article made rationale for selecting the measuring circuit. The choice of the main hardware components. Describes a method to accomplish the task with the use of a programmable logic array. In operation, is implemented the algorithm programmable logic array in the language of Verilog. There are examples of programs. The result has been designed digital test signal generator for impedance meter.
Keywords: programmable integrated circuit; algorithm; measuring and equivalent circuits; schematic diagram; software module; digital circuit